A retrospective study on clinical profile and outcome of respiratory cause of ventilation in children with age group between 1 month to 5 years in pediatric intensive care unit of a tertiary centre hospital - Vijay Kulkarni; B M Manasa (Wolters Kluwer Medknow Publications, 2017)
Introduction: Mechanical ventilation has become frequently used life supportive management in Pediatric Intensive Care Units (PICU) Objectives: To determine the characteristics, common cause for ventilation, Ventilation related complications and final outcome of ventilated patients in PICU, SDM Material and Methods: A retrospective study on ventilated children for respiratory cause, admitted to PICU from 1st Dec 2015 to 31st May 2016.The factors studied include demographic and clinical profile, length of stay on ventilator, indication for ventilation, complication and the final outcome. Results: A total of 170 case admitted in PICU were ventilated over the period of six months. Male to female ratio was 2.9:1. Impending respiratory failure (34.7%) and respiratory distress with underlying pneumonia (26.08%) causes were found to be the commonest indication of ventilation in the study. 39.13% of patient had required ventilation on the same day of admission, Average ventilator stay falls between >24hrs to 72hours. 17.39% ventilator associated pneumonia and 17.39% sepsis positive, 43.47% of ventilated case were recovered and successfully discharged and 56.5% of death among all the cases. Conclusions: Study provides an insight into early referral of sick cases to tertiary centre and early intervention.